The Influence of Pop-Up Book Media on Reading Interest of Students of Fiqh Subject Class V MI Raden Rahmat Ngerong Pasuruan (SCHOOLAR: Social and Literature Study in Education, 2023)
One of the important subjects in the world of education is Islamic Religious Education. The importance of Islamic Religious Education in schools is to encourage and hone students so that they can always understand the teachings of Islam as a whole. One of the most important aspects of Islamic Religious Education is Fiqh. Media Pop-Up Books are Media books that demonstrate the potential for movement and interaction through the use of paper as a material for folding, rolling, shaping, wheeling or rotation. The purpose of this study was to find out how the effect of using Pop-Up Book Media on students' reading interest in Fiqh subjects in class V MI Raden Rahmat Ngerong Pasuruan. This research is a type of quantitative research, where the quantitative approach emphasizes the analysis only on numerical data (numbers) starting from data collection, interpretation of the data and the appearance of the results which are processed by statistical methods. The subject of this study was a sample of 15 students of MI Raden Rahmat Ngerong Pasuruan. In this study, the dependent variable is reading interest (Y). Meanwhile, in this study, the independent variable is Media Pop Up Book (X). In this study, it was found that there was a significant correlation with the result, which was 0.964. The result is that the calculated r value is greater than the table r in the calculation of the product moment correlation. This shows that the Pop-Up Book media has an influence on students' reading interest in Fiqh subjects in Class V MI Raden Rahmat Ngerong Pasuruan.